Banking 'development': the geopolitical–economy of infrastructure financing. Issue 3 (3rd July 2021) - Anguelov, Dimitar
ABSTRACT: In the post-2008 global economy, infrastructure development and financing have risen to the top of the development agenda, emerging as a contested field for global investments involving seemingly divergent interests, objectives, rationalities and practices. Whereas multilateral development banks such as the World Bank advocate the market-based public–private partnership aimed at attracting private finance and deepening marketized governance, China is forging a state-capitalist alternative through its Belt and Road Initiative (BRI). These models are far from mutually exclusive. Through a conjunctural approach, the paper examines the broader trade and financial interdependencies in which these models are entangled, and the geopolitical–economic objectives enframing the emergent infrastructure regime. These are explored vis-à-vis Indonesian infrastructure projects, framed by competition between China and Japan.